La Contribución de Kant a la Psicoterapia.: La importancia de los escritos de Kant en la tradición de la investigación ética en el campo de la psicoterapia. - Sánchez Blanco, Lorena (Revista de Psicoterapia, 2019)
The study and integration of the ethics into the psychotherapeutic realm has a fundamental role in order to help therapist to take right decisions that will affect to the wellbeing of clients. For the purpose of this article Kant’s perspective of Ethics is considered in order to offer a guidance to practitioners and to facilitate the resolution or understanding of ethical dilemmas that may arises within the psychotherapeutic encounter. Criticism to his work are taken into account with the aim to expand his view and to include the role of the emotions in the study of ethics and psychotherapy.